MATHEMATICAL METHOD OF COMPOSING AND CORRECTION OF CURRICULUMS - Литвиненко, О. Є.; Масловский, Б.Г. (Science-based technologies, 2016)
A mathematical model of the problem, including a target function and a system of limitations, is presented. The bivalent values that determine distribution of educational disciplines among semesters are chosen to be the sought variables. The target function reflects the aspiration to minimize deviation of the planned order of teaching of disciplines from the most preferable order, defined on the basis of methodical considerations. The system of limitations reflects the basic requirements applied to the curriculum: including all the specified disciplines into the curriculum; compliance to the normative requirements to the quantity of disciplines, examinations, course projects and course works in each semester; to the general volume of auditory lessons and to the amount of auditory lessons in alternative disciplines per week; to the general amount of training hours for all disciplines in each semester; to the sequence of teaching of educational disciplines. It is proven that the problem of composing and correction of curricula is reduced to the class of extreme combinatorial problems with linear structure. This provides an opportunity of using the effective algorithms of directed search for its solution.